What drives digital marketers toward using generative AI: An investigation of the factors influencing adoption of ChatGPT and direction for future research - Mollik, Md. Soleman; Faruk, Mohammad; Rahman, Md. Masudur (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Generative artificial intelligence (AI) is revolutionizing digital marketing by enabling content creation, customer engagement, and strategic decision-making at unprecedented speed and scale. Yet, despite its transformative potential, research on the factors driving marketers’ adoption of generative AI tools such as ChatGPT remains scarce, particularly in emerging economies. Against this backdrop, this study aims to investigate the determinants influencing digital marketers’ adoption of ChatGPT and chart directions for future research. Quantitative research design was employed, drawing on constructs from the TAM and the UTAUT, while incorporating contextual variables such as industry influence, organizational culture, and perceived credibility. Data were collected from 500 digital marketers in Bangladesh using convenience sampling and analyzed using PLS-SEM. The findings reveal that performance expectancy, awareness, effort expectancy, and industry influence significantly shape attitudes toward ChatGPT, whereas organizational culture does not play a significant role. Attitude and perceived credibility emerged as the strongest predictors of actual usage, underscoring the centrality of favorable perceptions and trust in adoption behavior. The chapter makes threefold contributions. Academically, it extends adoption models by highlighting contextual variables in the adoption of AI. Practically, it offers guidance for marketers and organizations to build trust and showcase performance benefits. At the policy level, it calls for regulatory frameworks ensuring credibility and responsible use. Collectively, the study enriches understanding of generative AI adoption and lays a foundation for future research in this rapidly evolving field.